(untitled) (Journal of Human Sciences, 2024)
The relationship between the two languages ​​is of great significance, and the similarity between the two languages ​​goes beyond their borders to the similarity between Hausa and other Semitic languages, such as Himyaritic, Kaduna, and Aramaic. This fully indicates that the Hausa language has a close relationship with the Semitic languages ​​and the Arabic language in particular. The study addressed the similarities in words, grammatical vocabulary, and morphology between the Arabic and Hausa languages ​​used in the city of Kano, located in the north of Nigeria, as well as defining the word Hausa and the countries that speak the Hausa language and its spread around the world, along with mentioning the universities that teach this language.